SAT0206 Role of Tissue Doppler Echocardiography in Detecting Preclinical Cardiac Involvement in Systemic Sclerosis Patients. (23rd January 2014) - Limonta, M.; Lupi, E.; Gori, M.; Scuri, P.; Baio, P.; Duino, V.; Gavazzi, A.; Senni, M.
Abstract : Background: Primary myocardial involvement is common in systemic sclerosis (SSc), but often underestimated. Clinically apparent myocardial involvement has significant therapeutic implications and is considered an important prognostic factor. Cardiac involvement may occur years before clinical manifestation. Limited data are available on preclinical cardiac involvement assessment. In this study we investigated whether preclinical cardiac dysfunction can be detected by echocardiographic Tissue Doppler Imaging (TDI) in SSc patients. Methods: We prospectively studied 33 consecutive female patients (mean age ±SD 48.6±8.5 years)with SSc, without pulmonary hypertension, arterial hypertension or renal failure, and in I NYHA class. Results were compared with 16 age and sex-matched healthy controls (mean age ±SD 48.8 ±5.6 years; p=0.93). patients underwent standard echocardiography, along with measurements of longitudinal velocities by TDI to assess right ventricular and left ventricular (LV) contractility and LV diastolic function. Results: Systolic right ventricular function, as measured by peak systolic tricuspid annular velocity, was lower in patients than in controls (mean±SD 13.3±2% vs 14.8±1.4%; p<0.01). PASP was higher in the patient group (mean±SD 26.8±5.5% vs 20.8±2.9%; p<0.0001), even if within the normal range. Patients with SSc had a worse LV relaxation compared with the controls. Medial mitral annulus early diastolic velocity was lower in patients than in controls (patients: mean±SD 8.3±2.2%; controls 11.2±1.7%; p<0.00003), while E/E' was significantly higher (patients: mean±SD 10±2.3%; controls 7.4±1.5%; p<0.0002). Both groups had similar LV ejection fraction (patients: mean±SD 61.9±5.2%; controls 62.5±3.9%; p<0.67), while peak systolic mitral annular velocity as measured by TDI (medium value between septal, lateral, inferior and anterior ones) was significantly lower in patients than in controls (mean±SD 8.2±2% vs 10.1±1.1%; p<0.0005). Conclusions: Evaluation of ventricular function by TDI is an effective tool to detect preclinical systolic and diastolic cardiac involvement in SSc patients, when therapeutics are supposed to be more affective. Disclosure of Interest: None Declared